Embodied curriculum mapping as a foundation for critical self-reflection and culture change - Basu, Alo C. (Frontiers in Education, 2024)
This article describes a first-person qualitative research study to understand how common pedagogical approaches and cultural learning environments in STEM impact individuals. Prior to the study, the author observed that many students who were successful in advanced undergraduate neuroscience courses reported having struggled academically, socially, or emotionally in introductory STEM courses. The objective was to generate new ideas for approaches to address high rates of student attrition from introductory STEM courses related to this full range of issues through curriculum development. The author, a neurobiologist and tenured faculty member at the institution, audited four introductory STEM courses: Introduction to Cellular and Molecular Biology, Atoms & Molecules, Calculus 1, and Introductory Physics 2: Electromagnetism, Optics, and Modern Physics, offered by tenured colleagues in four different departments. A total of approximately 600 hours was spent by the author attending lectures, participating in classroom activities, completing homework, and studying for assessments. Homework, quizzes, and exams were marked by the course faculty using the same criteria as were applied for student work. In addition to measures of academic performance collected through the normal assessments, the author made note of her own emotional responses throughout the course of the study, which is why the process was dubbed ‘embodied’ curriculum mapping. The emotional responses revealed high levels of emotional stress associated with assessment, sensitivity to disciplinary boundary reinforcement, and a complex role of social and academic identity in all aspects of the experience. Given the first-person nature of the study, the potential future generalizability of the findings must be considered in light of the various revealed aspects of identity and experience of the author and subjected to further study using a broader range of empirical methodologies. The focus of this article’s conclusions and recommendations is therefore the impact of the process on the author and the potential for a similar process to serve as a foundation for critical self-reflection and learning for other STEM educators. The author recommends the process as a generative tool for pedagogical innovation and building faculty capacity for culture change in STEM.